2020
DOI: 10.20961/alchemy.16.2.40527.250-259
|View full text |Cite
|
Sign up to set email alerts
|

Sintesis dan Karakterisasi Nanokalsium Oksida dari Cangkang Telur

Abstract: <p>Pencegahan osteoporosis dilakukan dengan mengkonsumsi kalsium. Pada umumnya kalsium yang dikonsumsi dalam bentuk mikro kalsium. Ukuran mikro kalsium hanya diserap tubuh sekitar 50%, sehingga sering menyebabkan defisiensi. Sehingga, teknologi untuk membuat ukuran nanokalsium telah dikembangkan agar penyerapan kalsium dalam tubuh lebih besar. Penelitian ini bertujuan untuk mensintesis nanokalsium dari cangkang telur yang merupakan limbah industri roti. Sintesis nanokalsium oksida dari cangkang telur den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…H. opuntia calcium extraction was done by following the method used by Habte et al (2019) and Sunardi et al (2020) with several modifications on the hydrochloric acid (HCl) and sodium hydroxide (NaOH) concentration used, as well as the calcination that was not done in this experiment. Dried H. opuntia was cleaned first from dirt and then ground into crude powder using a chopper (Han River HRJRJ-S2BK, China).…”
Section: Calcium Extractionmentioning
confidence: 99%
“…H. opuntia calcium extraction was done by following the method used by Habte et al (2019) and Sunardi et al (2020) with several modifications on the hydrochloric acid (HCl) and sodium hydroxide (NaOH) concentration used, as well as the calcination that was not done in this experiment. Dried H. opuntia was cleaned first from dirt and then ground into crude powder using a chopper (Han River HRJRJ-S2BK, China).…”
Section: Calcium Extractionmentioning
confidence: 99%
“…The OHabsorption has a small and separate intensity, this is presumably due to the high heating temperature so that the OHgroup will experience decomposition. Hardiyanti (2013) showed that the higher the heating temperature, the OHgroup would disappear and β-TCP would form.…”
Section: Table 1 Crystallinity Of Hap At Various Sintering Temperaturesmentioning
confidence: 99%
“…Siregar (2020) [40] synthesized fluorapatite from chicken eggshells using the hydrothermal method with a sintering temperature of 600 °C for 2 hours. Fluorapatite was also successfully synthesized by Sari (2018) [41] from duck eggshells using the microwave irradiation method with a sintering temperature of 600 °C for 2 hours. The resulting fluorapatite has a spongy morphology, is irregular, and forms agglomerates.…”
Section: Figure 6 Crystal Size and Percentage Of Crystallinity Of Flu...mentioning
confidence: 99%